2013
DOI: 10.1242/dev.098590
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors lhx1/5-1 and pitx are required for the maintenance and regeneration of serotonergic neurons in planarians

Abstract: SUMMARYIn contrast to most adult organisms, freshwater planarians can regenerate any injured body part, including their entire nervous system. This allows for the analysis of genes required for both the maintenance and regeneration of specific neural subtypes. In addition, the loss of specific neural subtypes may uncover previously unknown behavioral roles for that neural population in the context of the adult animal. Here we show that two homeodomain transcription factor homologs, Smed-lhx1/5-1 and Smed-pitx,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
169
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(189 citation statements)
references
References 73 publications
20
169
0
Order By: Relevance
“…Analyses of the planarian photoreceptor, excretory and serotonergic cells have shown that tissue-specific transcription factors are detected in the stem cells in intact (Lapan and Reddien, 2012) and regenerating tissues (Lapan and Reddien, 2011;Scimone et al, 2011;Currie and Pearson, 2013); these studies have identified the first sets of precursor cells in planarians outside of the germ cells (Newmark et al, 2008) and have generated a working model in which planarians possess diverse lineage-committed progenitors that contribute to the maintenance and regeneration of tissues (Reddien, 2013;Rink, 2013). In contrast to the well-defined excretory system and photoreceptors, the nervous system represents a formidable challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analyses of the planarian photoreceptor, excretory and serotonergic cells have shown that tissue-specific transcription factors are detected in the stem cells in intact (Lapan and Reddien, 2012) and regenerating tissues (Lapan and Reddien, 2011;Scimone et al, 2011;Currie and Pearson, 2013); these studies have identified the first sets of precursor cells in planarians outside of the germ cells (Newmark et al, 2008) and have generated a working model in which planarians possess diverse lineage-committed progenitors that contribute to the maintenance and regeneration of tissues (Reddien, 2013;Rink, 2013). In contrast to the well-defined excretory system and photoreceptors, the nervous system represents a formidable challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in flies and crustaceans, sim functions as a master regulator of midline cells by regulating the specification of midline progenitors (Nambu et al, 1991;Vargas-Vila et al, 2010), whereas in vertebrates, sim controls the differentiation (Michaud et al, 1998;Eaton and Glasgow, 2006) and migration (via plexinC1) (Xu and Fan, 2007) (Lapan and Reddien, 2012), protonephridia (Scimone et al, 2011), serotonergic (Currie and Pearson, 2013) and novel CNS (bHLH) progenitors, respectively. *Progenitors that are only observed during regeneration.…”
Section: Identification Of Neuronal Progenitor Cells In Planariansmentioning
confidence: 99%
See 2 more Smart Citations
“…First, in ecdysozoan lineages, Nodal appears to have been lost (7, 9), whereas Pitx is generally symmetrically expressed (8) and, where studied, does not function in LR asymmetry (10, 11). Second, some lophotrochozoans do not show asymmetric Pitx expression (8,12,13). Third, functional studies on protostome Nodal signaling are currently restricted to molluscs (5), so it is unclear whether the regulatory connection between Nodal and Pitx is conserved even in those species that show asymmetric expression.…”
mentioning
confidence: 99%